2011
DOI: 10.1007/s11356-011-0537-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pH and temperature on the biosorption of lead(II) and cadmium(II) by sodium-modified stalk sponge of Zea mays

Abstract: The results showed that the modified stalk sponge of Z. mays had a good capacity for biosorption of Pb(II) and Cd(II). The kinetic behavior was described by the pseudo-second-order model for both metallic species. The experimental isotherms obtained at different temperatures were fit with Langmuir and Freundlich models. Thermodynamic parameters ΔH(0) and ΔS(0) were calculated using the van't Hoff equation, and the results show that Pb(II) and Cd(II) sorption by modified stalk sponge of Z. mays is an exothermic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…The removal of Cd and Pb was the highest in basic conditions, but this increase could be explained by metal precipitation due to formation of metal hydroxides at these pH values [2931]. At highly acidic conditions, Cd and Pb removal showed a lower metal uptake; this behavior could be attributed to competition for metal binding sites between metal ions and hydrogen (H + ) and hydronium (H 3 O + ) ions because it has been established that the hydrogen ion is a strong competing adsorbate [31, 32]. Moreover, the p K a values for the carboxylic groups of the α -L-guluronic acid and β -D-mannuronic acid of the alginate have been reported to be in the range of 3.4 to 3.9 [33], which indicates a positive charge of the biosorbent below these values that results in a decrease of metal biosorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal of Cd and Pb was the highest in basic conditions, but this increase could be explained by metal precipitation due to formation of metal hydroxides at these pH values [2931]. At highly acidic conditions, Cd and Pb removal showed a lower metal uptake; this behavior could be attributed to competition for metal binding sites between metal ions and hydrogen (H + ) and hydronium (H 3 O + ) ions because it has been established that the hydrogen ion is a strong competing adsorbate [31, 32]. Moreover, the p K a values for the carboxylic groups of the α -L-guluronic acid and β -D-mannuronic acid of the alginate have been reported to be in the range of 3.4 to 3.9 [33], which indicates a positive charge of the biosorbent below these values that results in a decrease of metal biosorption.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum amount of Cd adsorbed by CAB increased slightly with an increase in temperature. This behavior could be due to the surface binding reactions that occur simultaneously with changes in temperature [32] and it indicates that calcium alginate beads have a greater affinity for Cd when the temperature increases (Figure 6). It was reported that cadmium biosorption by different types of biosorbents was weakly affected by temperature in the test range of 20°C to 50°C [27, 32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high concentrations, Pb has adverse effects on plant morphology, growth and photosynthesis (García‐Rosales et al . ; Pidatala et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…La cáscara de maní se usa en la remoción de Cu(II) y Cr(III) [13]. También, se usan residuos de maíz en la remoción de Cd(II) y Pb(II) [14]. La vaina de cacao, el tallo de plátano, las cáscaras de arroz y de coco, la corteza de papaya y melón, residuos de soya, las semillas de uva y las cáscaras de nuez y moringa, entre otras, se usan también en la remoción de Pb(II) [15].…”
Section: Introductionunclassified